DEVELOPMENT OF CREATIVE ABILITIES OF PRESCHOOL CHILDREN THROUGH UNCONVENTIONAL METHODS (European Journal of Interdisciplinary Research and Development, 2023)
This article presents methods for developing the creative abilities of preschool children from 3 to 7 years old through various non-traditional drawing methods.